Teacher Resilience Strategies Between Theory and Practice in Tanzanian Secondary Schools - Joseph Mpemba; Anthony Sichone; Abdulkarim Kiswanya (Universitas Majalengka, 2025)
Teacher resilience is critical for educational quality, particularly in resource-constrained environments where educators face substantial systemic challenges. This study examined teachers' perceptions of effective resilience strategies in challenging educational contexts within secondary schools in Morogoro Municipality, Tanzania. Employing a pragmatic mixed-methods convergent parallel design, data were collected from 236 participants comprising 234 teachers (selected through simple random sampling) and 2 key informants (purposively sampled). Quantitative data were gathered using validated Likert-scale questionnaires, while qualitative insights emerged from semi-structured interviews. Data analysis involved descriptive and inferential statistics for quantitative data and thematic analysis for qualitative data, with subsequent integration of findings. The findings revealed significant skepticism toward organizational resilience strategies, with 67.9% of responses rating them as inadequate, contrasting with 55.5% rating practical pedagogical strategies as adequate. Teachers expressed particular doubt about creating positive school culture (39.8% disagreement) and fostering collegial relationships (30.3% disagreement), while valuing concrete approaches such as positive verbal reinforcement (60.2% agreement) and interactive learning (59.8% agreement). Qualitative data emphasized the importance of professional learning communities, mentorship networks, and self-care practices. The disconnect between theoretical frameworks and practical implementation suggests that resilience interventions must be contextually adapted, resource-conscious, and embedded within daily teaching practices. The study highlights critical policy gaps requiring comprehensive teacher support systems integrating professional development, mentorship, and wellness initiatives tailored to local contexts.